(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: Ducks suffer a huge economic loss as a result of infections with Pasteurella multocida and Riemerella anatipestifer, which cause high morbidity and mortality. Because these pathogens induce similar clinical symptoms when coinfections occur, it is very difficult to differentiate between them based just on clinical signs. Hence, these major pathogens must be quickly and accurately detected. Materials and Methods: A total of 104 birds ranging from 2 days to 4 weeks old were collected from Egyptian farms, and the outcomes were compared statistically. Conventional cultural identification procedures and a direct multiplex polymerase chain reaction assay were utilized to recognize both pathogens in a single tube reaction simultaneously. Then, the obtained isolates were characterized phenotypically and genotypically. Results: Clinical signs appear at 2–4 weeks of age with respiratory distress (dyspnea), white fluid feces, and stunting. The scrutinized data demonstrated a significantly higher detection rate by PCR directly compared to classical culture procedures. Pasteurella multocida was detected only by PCR. The disc diffusion technique against ten antibiotics showed absolute susceptibilities to amikacin, doxycycline, and florfenicol. High levels of beta-lactam resistance were observed. Riemerella anatipestifer isolates were screened for pathogenicity and plasmid-borne blaTEM genes. All six isolates harbored five virulence genes: aspC, RA46, m28, pstS, and Nlp/P60. Moreover, blaTEM was identified into four isolates and deposited to GenBank with accession numbers OP347083, OP347084, OP347085, and OP347086. Conclusion: These results suggest advanced PCR assays can be applied to the field for rapid and valuable diagnosis of two significant pathogens and focus on the worth of ducks in the propagation of transferable antibiotic resistance genes into the environment. J. Adv. Vet. Anim. Res., 10(2): 211–221, June 2023 http://doi.org/10.5455/javar.2023.j671